Statistical characterization of atmospheric PM10 and PM2.5 concentrations at a non-impacted suburban site of Istanbul, Turkey - Karaca, F; Alagha, O; Ertürk, F (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Inhalable particulate matter (PM10) has been monitored at several stations by Istanbul Municipality. On the other hand, information about fine fraction aerosols (PM2.5) in Istanbul atmosphere was not reported. In this study, 86 daily aerosol samples were collected between July 2002 and July 2003. The PM10 annual arithmetic mean value of 47.1 mu g m(-3), was lower than the Turkish air quality standard of 60 mu g m(-3). On the other hand, this value was found higher than the annual European Union air quality PM10 standard of 40 mu g m(-3). Furthermore, the annual mean concentration Of PM2.5 20.8 mu g m(-3) was found higher than The United States EPA standard of 15 mu g m(-3). The statistics and relationships of fine, coarse, and inhalable particles were studied. Cyclic behavior of the monthly average concentrations of PM10 and PM2.5 data were investigated. Several frequency distribution functions were used to fit the measured data. According to Chi-squared and Kolmogorov-Smirnov tests, the frequency distributions Of PM2.5 and PM10 data were found to fit Log-logistic functions. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: PM10; PM2.5; statistical analysis; frequency distribution; air pollution; PARTICULATE MATTER; MAJOR IONS; POLLUTION; MORTALITY; ADULTS; Environmental Sciences & Ecology